Translating worlds
1 online resource.
Keywords: "This international and interdisciplinary volume explores the relations between translation, migration, and memory. Examining the connections between translation, memory, and migration, the volume brings together humanities researchers from a range of disciplines including history, museum studies, memory studies, translation studies, and literary, cultural, and media studies. The innovatory perspective adopted by Translating Worlds understands translation's explanatory reach as extending beyond the comprehension of one language by another to encompass those complex and multi-layered processes of parsing by means of which the unfamiliar and the familiar, the old home and the new, are brought into conversation and connection. Themes discussed include: · How memories of lost homes act as aids or hindrances to homemaking in new worlds; · How cultural memories are translated in new cultural contexts; · Migration, affect, memory, and translation · Migration, language, and transcultural memory; Migration, traumatic memory, and translation. This edited volume will appeal to humanities researchers and students interested in translation, history, memory studies, literary, cultural and media studies"--